Above-threshold ionization driven by Gaussian laser beams: beyond the electric dipole approximation. (11th August 2021) - Böning, B; Fritzsche, S
Abstract: Strong-field atomic experiments have recently become sensitive to nondipole (magnetic) interactions. In particular, photoelectrons emitted in above-threshold ionization possess a nonzero momentum along the beam axis as a result of the Lorentz force. Here, we show how this longitudinal momentum can be theoretically calculated based on a nondipole strong-field approximation that accounts not only for the temporal but also the spatial dependence of the laser field in the photoelectron continuum. If the driving laser beam is approximated as a plane wave, the theoretical values differ from known experimental results by a constant offset. We demonstrate that this offset can successfully be removed if a realistic Gaussian beam profile is accounted for in the quantum description of ATI. We also discuss the influence of the size of the beam waist in the focus.